Monocytes, Peripheral Blood Mononuclear Cells, and THP-1 Cells Exhibit Different Cytokine Expression Patterns following Stimulation with Lipopolysaccharide - Anita Schildberger; Eva Rossmanith; Tanja Eichhorn; Katharina Strassl; Viktoria Weber (Hindawi Limited, 2013)
THP-1 cells are widely applied to mimic monocytes in cell culture models. In this study, we compared the cytokine release from THP-1, peripheral blood mononuclear cells (PBMC), monocytes, or whole blood after stimulation with lipopolysaccharide (LPS) and investigated the consequences of different cytokine profiles on human umbilical vein endothelial cell (HUVEC) activation. While Pseudomonas aeruginosa-stimulated (10 ng/mL) THP-1 secreted similar amounts of tumor necrosis factor alpha (TNF-α) as monocytes and PBMC, they produced lower amounts of interleukin(IL)-8 and no IL-6 and IL-10. Whole blood required a higher concentration of Pseudomonas aeruginosa (1000 ng/mL) to induce cytokine release than isolated monocytes or PBMC (10 ng/mL). HUVEC secreted more IL-6 and IL-8 after stimulation with conditioned medium derived from whole blood than from THP-1, despite equal concentrations of TNF-α in both media. Specific adsorption of TNF-α or selective cytokine adsorption from the conditioned media prior to HUVEC stimulation significantly reduced HUVEC activation. Our findings show that THP-1 differ from monocytes, PBMC, and whole blood with respect to cytokine release after stimulation with LPS. Additionally, we could demonstrate that adsorption of inflammatory mediators results in reduced endothelial activation, which supports the concept of extracorporeal mediator modulation as supportive therapy for sepsis.